Violation of rights and reproduction of violence in Latin America - MORÁS, Luis Eduardo (Utopía y Praxis Latinoamericana, 2023)
The tragedy of the extraordinary death figures experienced in Latin America due to the covid-19 pandemic, comes in addition to the already known numbers of violent deaths produced within the framework of an overwhelming crime rate and the high mortality rates resulting from the appalling conditions. life of broad sectors of society; dramatic picture where boys, girls, adolescents and young people stand out as the most affected groups. At the same time, in recent decades, a significant number of Conventions and Treaties have been approved in order to guarantee the full validity of Human Rights. The article, based on the review and analysis of secondary sources, expose the notorious distance between the declared intentions of a legislation that does not prevent the reproduction of a reality characterized by processes of profound exclusion and generalized violence.